Kurikulum Pendidikan Islam Di UIN Malang : Studi Pemikiran Imam Suprayogo Dan M. Zainuddin - Firda Sofiana; Benny Afwadzi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Islamic Education Curriculum in UIN Malang: A Study of Imam Suprayogo and M. Zainuddin Thought.In fact, the world of Islamic education has full of problems, both the dichotomy of sciences and the decline in morality and religiosity of Muslims, so efforts are needed to resolve these problems. the authors analize two figures from UIN Malang, namely Imam Suprayogo and M. Zainuddin towards this goal. This article is the result of library research whose data are taken from primary sources of their works, such as Pendidikan Berparadigma Al- Qur’an by Imam Suprayogo and Paradigma Pendidikan Terpadu by M. Zainuddin and enhanced by interviews. By using descriptive-analytical method, the authors conclude that their thoughts are progressive and dynamic, have proactive and anticipatory educational insights in facing the accelerated development of science and technology, the demands of change, and are future oriented. The characteristics of his thinking appear in the need to develop an Islamic education curriculum into an integrated curriculum. Imam Suprayogo with his tree of knowledge, and M. Zainuddin with his Point Vortex Theory. Furthermore, their thoughts related to the Islamic education curriculum can be used as a consideration and reference to be actualized and implemented in the development of Islamic education institutions.Abstract: Kurikulum Pendidikan Islam di UIN Malang: Studi Pemikiran Imam Suprayogo dan M. Zainuddin.Hakikatnya dunia pendidikan Islam penuh dengan masalah, baik adanya paham dikotomi ilmu pengetahuan maupun turunnya moralitas dan religiusitas orang Islam, sehingga perlu upaya menyelesaikan masalah itu. Tokoh dari UIN Malang, yakni Imam Suprayogo dan M. Zainuddin membahas hal ini. Metode penulisan menggunakan library research yang data-datanya diambil dari sumber primer karya-karya keduanya, seperti Pendidikan Berparadigma Al- Qur’an karya Imam Suprayogo dan Paradigma Pendidikan Terpadu karya M. Zainuddin serta disempurnakan dengan wawancara. Dengan menggunakan metode deskriptif-analitis, penulis menyimpulkan bahwa pemikiran keduanya bersifat progresif dan dinamis serta memiliki wawasan kependidikan yang proaktif dan antisipatif dalam menghadapi percepatan perkembangan ilmu pengetahuan dan teknologi, tuntutan perubahan, dan bersifat future oriented. Ciri-ciri pemikirannya nampak pada perlunya pengembangan kurikulum pendidikan Islam menjadi kurikulum terintegrasi. Imam Suprayogo dengan pohon ilmunya, dan M. Zainuddin dengan Point Vortex Theory-nya. Lebih lanjut, Pemikiran mereka terkait kurikulum pendidikan Islam dapat dijadikan pertimbangan dan rujukan untuk diaktualisasikan dan diimplementasikan dalam pengembangan kelembagaan pendidikan Islam.